2023
DOI: 10.1177/2329048x231200613
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SOX1 Antibodies in a 3-Year-old Girl, Post-Varicella

Aline Wijnand,
Helene Verhelst

Abstract: Anti-SRY-related HMG-box gene 1 (SOX1) antibodies were initially described in adults with paraneoplastic neurological disorders, where they are considered high-risk onconeural autoantibodies. Only two pediatric cases of anti-SOX1 antibodies have been reported: a 17-year-old adolescent presenting with paraneoplastic limbic encephalitis due to Hodgkin lymphoma and a 12-year-old girl presenting with non-paraneoplastic encephalitis. We present a unique case of anti-SOX1 antibodies in a 3-year-old girl, post-varice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The patient showed favorable clinical course, with rapid improvement of symptoms. This case report represents that SOX-1 antibodies may be found also in childhood after viral infections like varicella [16]. Within this cases of ICIs relevated encephalitis, Gao Y. et al [4] reviewing English literature in the Pub Med database published to 2022 found 50 cases of ICIs-associated autoimmune encephalitis, the majority of these cases had lung cancer 20/50 (40%).…”
Section: Discussionmentioning
confidence: 79%
“…The patient showed favorable clinical course, with rapid improvement of symptoms. This case report represents that SOX-1 antibodies may be found also in childhood after viral infections like varicella [16]. Within this cases of ICIs relevated encephalitis, Gao Y. et al [4] reviewing English literature in the Pub Med database published to 2022 found 50 cases of ICIs-associated autoimmune encephalitis, the majority of these cases had lung cancer 20/50 (40%).…”
Section: Discussionmentioning
confidence: 79%